UNPACKING THE EFFECTS OF DIGITAL TRANSFORMATION ON CUSTOMERSATISFACTION AND WELL-BEING: INSIGHTS FROM BSI’S PLATFORM TRANSITION TO BYOND - Umaimah 'Affaf; Nanik Wahyuni; Meldona; Desi Sari Ayuni (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2026)
Abstract (English version) Objective – This study aims to evaluate user satisfaction with the BYOND by BSI application. This research not only aims to assess user satisfaction with the BYOND by BSI application but also to evaluate its contribution to customer welfare, both from a financial aspect (transaction efficiency and accessibility) and a spiritual aspect (value of blessings and ease of worship through prayer time, zakat, and charity features). Methodology – The research method used is a qualitative approach with a case study type. Data were obtained through in-depth interviews, participatory observations, and documentation studies involving eight informants consisting of active BYOND by BSI customers and internal BSI parties. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Research Results – The research results show that the majority of customers welcomed BSI's digital transformation positively due to the ease of access and the The research results show that the majority of customers responded positively to BSI's digital transformation, mainly due to the ease of access and the modern design of the application. The term modern application refers to an intuitive and user-friendly interface, faster navigation, integrated features within a single platform, and enhanced visual design that improves user experience. In addition, BYOND by BSI is considered superior due to its more comprehensive digital services, improved system performance, better security features, and its ability to provide a more seamless and efficient banking experience compared to the previous application. This study also highlights its novelty, as qualitative research exploring user experiences and perceptions of the BYOND by BSI application particularly during the transition from BSI Mobile remains limited and has not been extensively examined in previous studies.However, technical issues such as connection disruptions and slow authentication processes were still found, which impacted user satisfaction perceptions. The factors of perceived ease of use and perceived usefulness have been proven to affect customer satisfaction. Limitations – This study is limited to a qualitative approach involving eight informants, so the findings cannot be broadly generalized. The study also focuses on user experiences during the early transition period to BYOND by BSI without quantitative measurement of user satisfaction levels. Practical Implications – he implications of this research indicate that the success of Islamic banking digital transformation depends not only on technological innovation but also on system reliability and consistent user experience. Theoretically, it reinforces technology acceptance and service quality theories. Institutionally, it provides insights for BSI to enhance digital governance and service quality. Practically, it supports increased public trust and wider adoption of digital banking services. Originality/value - This study extends the Technology Acceptance Model by integrating maqashid sharia to explain digital banking adoption, trust, satisfaction, and multidimensional customer welfare.